2021
DOI: 10.3389/fimmu.2020.607166
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Diurnal Pattern of Salivary C-Reactive Protein (CRP) With Modest Associations to Circulating CRP Levels

Abstract: C-reactive protein (CRP), a humoral component of the innate immune system with important functions in host-defense, is extensively used as a sensitive biomarker of systemic inflammation. During inflammation, hepatocyte-derived CRP rises dramatically in the blood due to increased interleukin-6 (IL-6) levels. Reliable detection of CRP in saliva, instead of blood, would offer advantages regarding sampling procedure and availability but using saliva as a diagnostic body fluid comes with challenges. The aims of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The salivary CRP levels were higher at wake‐up than 45 min post‐awakening, and this pattern was consistent across consecutive days and 4 weeks. The results are consistent with the previous studies on the stable and distinctive diurnal salivary CRP patterns in the general population across days (Izawa et al, 2013; Out et al, 2012; Wetterö et al, 2020). While diurnal variation is less often observed in serum samples (Meier‐Ewert et al, 2001), our present findings underscore the importance of accounting for the potential circadian rhythm of salivary CRP to ensure comparability of results across studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The salivary CRP levels were higher at wake‐up than 45 min post‐awakening, and this pattern was consistent across consecutive days and 4 weeks. The results are consistent with the previous studies on the stable and distinctive diurnal salivary CRP patterns in the general population across days (Izawa et al, 2013; Out et al, 2012; Wetterö et al, 2020). While diurnal variation is less often observed in serum samples (Meier‐Ewert et al, 2001), our present findings underscore the importance of accounting for the potential circadian rhythm of salivary CRP to ensure comparability of results across studies.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike cytokines, salivary and serum CRP are likely to correlate as their origin is mainly in the liver (Slavish et al, 2015). While moderate to high positive correlations have been found between serum CRP and saliva CRP in some studies (Pay & Shaw, 2019;Wetterö et al, 2020), other studies (Dillon et al, 2010;Mirzaii-Dizgah et al, 2012) have found weak to nonsignificant correlations. The collection of noninvasive saliva samples is less expensive than serum samples and allows for repeated collections of this inflammatory biomarker and investigation of diurnal variations.…”
Section: Introductionmentioning
confidence: 98%
“…Salivary CRP has also been shown to be significantly higher in obese than in normal weight children ( 50 , 55 ), and to discriminate between lower and higher BMI in healthy adults when grouped in low sCRP vs. high sCRP ( 30 ). However, in the latter study, no significant correlation between BMI and the continuous sCRP measurement was detected ( 30 ), and Wettero et al ( 52 ) did not confirm a significant association between sCRP and BMI in middle-aged participants. To further evaluate the validity of both the correlation between DBS CRP and sCRP and each measurement itself, we split our sample into three BMI percentile range groups: A: ≤ 25, B: 26–74, C: ≥ 75.…”
Section: Discussionmentioning
confidence: 66%
“…The half-life of CRP in the circulation is very short, about 19 h, and decreases rapidly after the relief of the acute reaction. Therefore, CRP is widely used in clinical practice as an important marker of acute infection ( 33 ).…”
Section: Discussionmentioning
confidence: 99%